Design of an IT Asset Monitoring Application: Case Study at PT PLN UITJBT IT Division - Shidiq, Muhamad Rafli; Ruchiyat, Uyu Wachyu (STMIK Triguna Dharma, 2025)
Managing the history of IT assets is a crucial need for the IT Systems Division of PT. PLN (Persero) Central Java Transmission Unit. This study aims to design an application for monitoring asset history to improve efficiency and transparency. The Extreme Programming method was utilized, including iterative stages such as requirement analysis, design, testing, and implementation. The application is equipped with key features such as asset history management, data search, and real-time reporting. It allows administrators and users to track the lifecycle of each asset, including its acquisition, usage, maintenance, and disposal. Results indicate that the application enhances reporting speed and accuracy while minimizing data duplication risks. Additionally, the system can generate detailed reports that support decision-making processes, ensuring better planning and resource allocation. In conclusion, the application is expected to support more structured and effective asset management, improving overall productivity and helping PT. PLN's IT Systems Division maintain a more organized asset inventory.